A Crisis of Executive Managerialism in the EU: No Alternative? - Joerges, Christian; Weimer, Maria (Maastricht Faculty of Law Working Paper No. 2012-7, 2012)
Against a backdrop of rapidly evolving crisis management in the European financial and sovereign debt crisis this essay aims both to explore and to re-consider the role of law in the EU integration process: What did law accomplish? Where did it fail? What is law going to endure? What kind of future can it envisage? The essay traces back the evolution of the law-politics relationship in both EU legal scholarship and practice from the foundational period of ‘integration-through-law’ to the advent of ‘new governance’ in the EU, and finally to the current deep transformations of EU law in new economic governance and the financial crisis. The centrality of law as ‘both the object and the agent’ of European integration, and the legal enshrinement of EU’s economic constitution has recently neglected the weight of ‘the social’ in the societies of post-war Europe, a failure which was to become detrimental to both domestic social stability and the legitimacy of integration. Attempts to cure Europe’s social deficit by re-conceptualizing the notion of law as new governance have widened the theoretical perspective of EU legal scholarship. Yet new governance has not delivered more social democracy and justice in Europe in practical terms, and continues to suffer from the methodological problems of its ‘definition-by-contrast.’ These problems re-emerge in current new economic governance, which Europe’s crisis management is generating. This hybrid arrangement of hard and soft law instruments has, to date, been economically unsuccessful and socially disastrous, especially in the South of Europe. Equally disquieting, the notion of democratic law (either in traditional or experimentalist understandings) has been replaced by a praxis of authoritarian executive managerialism. The essay concludes by sketching out an alternative understanding of law-mediated legitimacy in the integration process, namely ‘conflicts-law constitutionalism’. This approach stresses the normative value of conflicts and pluralism in the process of European integration. Instead of ‘ever more Europe’ it aims to secure the existing democratic credentials of EU law, namely its ability to correct the democratic deficit of the Member States while respecting their constitutional integrity.
Keywords: EU economic constitution; EU financial crisis; European Union; governance; unity in diversity

Polanyi's Embeddedness and Shareholder Stewardship: A Contextual Analysis of Current Anglo-American Perspectives on Corporate Governance - Talbot, Lorraine E. (Social Science Research Network, 2012)
Polanyi saw the economy as properly embedded in society and argued that the capitalist free market, in commodifying social relations of production, seeks to disembed the economy from society. The resulting lack of continuity between society and economy, he maintained, created conflict which necessarily required state intervention. The market economy, therefore, in contrast to neoclassical/neoliberal economics’ vision of an autonomous, self-regulating market, required more, not less, state intervention to sustain it than alternative, more embedded economies. This article explores this conflict in the context of a specific neoliberal claim: that institutional shareholders are capable of being good “stewards” of the companies in which they invest. Utilising Polanyi’s embeddedness, this article assesses the “stewardship” approach as it is manifested in the US and in the UK. This approach is posited on a vision of a disembedded, self-regulating market. Putting it into practice is thus a retrograde step which will only exacerbate the problems created by the market-based corporate governance strategies which have prevailed since the late 1970s onwards.
Keywords: Polanyi; conflict; crisis; embeddedness; shareholder stewardship

Reconfiguring the Politics–Law Relationship in the Integration Project through Conflicts–Law Constitutionalism - Everson, Michelle; Joerges, Christian (European Law Journal, 2012)
This paper argues that the relationship between law and politics must be reconfigured within the European Union. Dissecting recent crises in economic, social and political organisation within Europe with reference to the three ‘fictitious’ commodities of Karl Polanyi, we find that law in Europe has contributed to de-legalisation, de-socialisation and disenfranchisement. Moving on to review the potential for law to respond to crisis through new paradigms of conflict resolution as suggested by Ralf Dahrendorf, we find that the steering capacity of law is nevertheless limited if it fails to establish a sustaining relationship with politics. Our conclusions are modest: conflict–law constitutionalism cannot solve Europe's many crises. However, it does represent a new paradigm of law within which relations between European law and European politics might be re-established—a vital step to overcoming crisis.
Keywords: European Union; constitutionalism; economic law; fictitious commodities

Processes of disembedding and displacement: anomie and the juridification of religio-ethnic identity in post-New Order Bali - Ramstedt, Martin (Asian Ethnicity, 2012)
This article applies Karl Polanyi's observation of a double movement of law in the history of nineteenth and early twentieth-century Europe to an analysis of Bali's integration into the global cultural economy. It describes how the increasing disembedding of the island's tourist industry from local norms and institutions, and the parallel disjuncture between Balinese religiosity and Indonesian state religion have created a condition of increasing collective anomie that has in turn provoked endeavors to juridify the Balinese religio-ethnic identity. Conceding the partial success of the juridification process that has been facilitated by the recent governance reform, and that has indeed effected a significant degree of re-embedding both tourism and religion into local culture, the article argues that not only has the anomic condition not been attenuated; the potential for internal conflict and division has even been enhanced.
Keywords: Bali; Balinese (Indonesian people); Europe; POLANYI, Karl, 1886-1964; anomie; decentralization; decentralization in government; disembedding; ethnicity; identity; juridification; religiousness

Shareholder Engagement in the Embedded Business Corporation: Investment Activism, Human Rights, and TWAIL Discourse - Dhir, Aaron (Business Ethics Quarterly, 2012)
The expansion of extractive corporations’ overseas business opera-tions has led to serious concerns regarding human rights–related impacts. As these apprehensions grow, we see a countervailing rise in calls for government interven-tion and in levels of socially conscious shareholder advocacy. I focus on the latter as manifested in recent use of the shareholder proposal mechanism found in corporate law. Shareholder proposals, while under-theorized, provide a valuable lens through which to consider the argument that economic behaviour is embedded within so-cial relations. In doing so, I situate my analysis within Third World Approaches to International Law (TWAIL) scholarship. Elsewhere, I have supported the use of corporate law tools in advancing the international human rights enterprise and argued that investment activism can be an essential component of this advancement. This paper represents a reflexive pause. Using the case study of a recent proposal submitted to Goldcorp Inc., I seek to problematize the shareholder proposal as a human rights advocacy tool and to examine it as a site of contestation.
Keywords: Third World Approaches to International Law; corporate accountability; corporate law; law; shareholder rights